Assessment of Hypertension and its Associated Factors among Type 2 Diabetes Mellitus Patients at Mirpur AJK (Medical Forum Monthly, 2021)
Objective: The objective of this study assessment of hypertension and its Associated Factors among Type 2 Diabetes Mellitus Patients at Mirpur AJK.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department Physiology, Biochemistry and Community Medicine of Mohtarma Benazir Bhutto Shaheed Medical College Mirpur, AJK from April 2018 to August 2019.Materials and Methods: In this study we included those patients who have diabetes mellitus and hypertension. It was cross section study, we selected 200 control normal subject free from hypertension and diabetes mellitus and 300 patients of diabetes mellitus with hypertension. We were taken the blood sample of patients and control. We centrifuge the sample and analyzed for fasting blood sugar and lipid profile (LDL, HDL, Cholesterol, TG). We also estimate urea, uric acid for both groups.Results: The BMI of the patients was higher than 25 kg/m2 and above (78.5%). and the mean systolic and diastolic blood pressure of T2DM patients were 135.8 mmHg (SD ± 25.9) and 87.5 mmHg (SD± 13.8) respectively. The lipid profile was higher in patients group as compare to control. Fasting glucose was higher in patients groups as compare to control. 78.5%) patients relied on oral hypoglycemic treatment in patients groups.Conclusion: The occurrence of hypertension was high. Only 27.8% of previously diagnosed hypertensive patients were normotensive. Age, BMI, and high lipid profile, cigarette smoking, residence and duration of T2DM were significantly associated with hypertension.